Effect of sintering environment to the physical properties of Al/calcined dolomite composite - Banjuraizah, Johar; N.A. Rejab; N.K. Su; M.S. Talib; Nur Maizatul Shima, Adzali; Mohamad Hatta, Musa; Alina Rahayu, Mohamed (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.